Analysis of risk factors for recurrence in infertile endometrial cancer patients after in vitro fertilization treatment - Wei, Hongyi; Pan, Ningning; Wang, Yang; Ma, Caihong (Frontiers in Endocrinology, 2023)
Purpose To investigate the oncologic outcomes of patients with early-stage endometrioid endometrial cancer (EEC) treated with in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) following fertility-sparing treatment (FST). Methods 62 patients who underwent IVF/ICSI treatment in a single fertility center between June 2010 and December 2021 after conservative treatment for early-stage EEC were assigned into a recurrence group and a non-recurrence group. The clinical characteristics and disease outcomes were retrospectively evaluated. Results The 62 women with complete remission (CR) after FST for EEC underwent 103 IVF cycles, resulting in 41 fresh embryo transfers (ETs) and 70 frozen-thawed transfers, 27 (43.55%) achieved clinical pregnancies, and 20 (32.26%) gave birth to a total of 23 live neonates. Additionally, 9 patients had live births from natural pregnancies after IVF failure, bringing the cumulative live birth rate to 46.77% (29/62). After a median follow-up period of 53.88 months (range 20.2-127.5 months), 17 patients (27.42%) experienced recurrence within 2.8 to 57.9 months after the first controlled ovarian stimulation (COS). The probabilities of relapse at 1, 2, and 3 years after the initiation of COS were 14.52% (9/62), 21% (13/62), and 25.81% (16/62), respectively. Factors such as the time to CR, the time to IVF, the frequency of COS, maintenance treatment before IVF , and histology type were not found to significantly affect recurrence (P=0.079, 0.182, 0.093, 0.267, and 0.41, respectively). Live births (HR: 0.28, 95%CI: 0.082-0.962, P=0.043) and the protocol of letrozole plus GnRH antagonist/agonist used during IVF (HR: 0.1, 95%CI: 0.011-0.882, P=0.038) were identified as independent favorable factors for recurrence. Conclusions Live birth was associated with decreased recurrence of EEC. Reducing estrogen levels during COS may serve to mitigate the risk of endometrial cancer recurrence.